Polymorphism of Amyloid Fibrils Induced by Catalytic Seeding: A Vibrational Circular Dichroism Study - Krupová, Monika; Kessler, Jiří; Bouř, Petr (Chemphyschem, 2021)
Amyloidal protein fibrils occur in many biological events, but their formation and structural variability are understood rather poorly. We systematically explore fibril polymorphism for polyglutamic acid (PGA), insulin and hen egg white lysozyme. The fibrils were grown in the presence of "seeds", that is fibrils of the same or different protein. The seeds in concentrations higher than about 5 % of the total protein amount fully determined the structure of the final fibrils. Fibril structure was monitored by vibrational circular dichroism (VCD) spectroscopy and other techniques. The VCD shapes significantly differ for different fibril samples. Infrared (IR) and VCD spectra of PGA were also simulated using density functional theory (DFT) and a periodic model. The simulation provides excellent basis for data interpretation and reveals that the spectral shapes and signs depend both on fibril length and twist. The understanding of fibril formation and interactions may facilitate medical treatment of protein misfolding diseases in the future.
Keywords: Insulin; vibrace; inzulin; vibrational circular dichroism; Polyglutamic Acid; protein folding; Density Functional Theory; Circular Dichroism; Vibration; katalýza; teorie funkcionálu hustoty; Muramidase; konformace proteinů; cirkulární dichroismus; catalytic seeding; amyloid; kyselina polyglutamová; Catalysis; Protein Conformation; molecular modeling; fibrous proteins; Amyloid; muramidasa